Repositório de recursos didáticos para o ensino investigativo de ciências em um laboratório biológico de aprendizagem - Arthur, Thalita (2025)
This doctoral thesis investigates the possibilities of using a digital repository of teaching resources in inquiry-based Science Education, through the implementation of a didactic sequence that explored the available materials, with an emphasis on the school garden as an educational space, referred to as the Biological Learning Laboratory, in the municipal school network of Passo Fundo, Brazil. The central problem that guides this study arises from students’ lack of interest in scientific subjects and the need to promote more contextualized, active, and meaningful pedagogical practices. Added to this scenario is the difficulty faced by teachers in locating supporting materials, often dispersed across different sources and not easily accessible in an integrated manner. To address this challenge, the research is grounded in theoretical frameworks that support the inquiry-based approach (Pedaste et al., 2015; Carvalho, 2013), active methodologies (Cunha et al., 2024; Moran, 2015; Dewey, 1979), and educational innovation (Chaves, 2022; Bacich; Moran, 2018), in line with the Brazilian National Common Curricular Base (BNCC), which emphasizes the development of competencies through interdisciplinary practices. The central research question is: can an inquiry-based Science practice, supported by a digital repository of teaching resources, foster the learning of elementary school students? The state-of-the-art analysis, carried out through dissertations addressing the use of school gardens in Science teaching, revealed not only the scarcity of studies articulating school gardens, inquiry-based teaching, and digital repositories, but also the fragmentation and dispersion of materials across multiple sources, which hinders teachers’ appropriation and effective use. In response, two complementary educational products were developed: a digital repository, organized into four main sections — Curricular Component, Successful Practices, School Garden, and User Guide — and a Teacher Support Guide to facilitate its use. The repository includes 47 teaching resources in diverse formats, such as 19 experimental activities, 18 videos, 2 simulators, 3 games, 3 informative texts, 1 structured lesson plan, and 1 supplementary material, thus offering a wide range of resources for Science teaching. This qualitative and exploratory research was conducted in three classes — two from the 7th grade and one from the 9th grade of elementary school — in a municipal school in Passo Fundo/RS. Data collection involved the classroom teacher’s logbook, direct observations, and analysis of the materials produced by students. Data analysis was guided by the conceptual framework of the inquiry cycle proposed by Pedaste et al. (2015) — Orientation, Conceptualization, Investigation, Conclusion, and Discussion — maintaining its original nomenclature due to its coherence with the methodological design implemented. The findings indicate that the digital repository significantly contributed to all stages of the inquiry cycle, proving to be a valuable resource for the development of pedagogical practices in disruptive learning environments. Its potential to support active methodologies, foster student engagement, promote critical thinking, and strengthen autonomy in knowledge construction was evidenced. It is concluded that the digital repository constitutes an effective tool to support teacher mediation, assisting in the implementation of innovative, collaborative, and integrated Science teaching practices. The educational product accompanying this thesis is available on the Educapes platform at the following address: http://educapes.capes.gov.br/handle/capes/1174414.